Prenatal Exposure to Gabapentin Alters the Development of Ventral Midbrain Dopaminergic Neurons - Alsanie, Walaa F.; Abdelrahman, Sherin; Alhomrani, Majid; Gaber, Ahmed; Habeeballah, Hamza; Alkhatabi, Heba A.; Felimban, Raed I.; Hauser, Charlotte A. E.; Tayeb, Hossam H.; Alamri, Abdulhakeem S.; Raafat, Bassem M.; Anwar, Sirajudheen; et al. (Frontiers in Pharmacology, 2022)
Background: Gabapentin is widely prescribed as an off-label drug for the treatment of various diseases, including drug and alcohol addiction. Approximately 83 to 95 % of the usage of gabapentin is off-label, accounting for more than 90 % of its sales in the market, which indicates an alarming situation of drug abuse. Such misuse of gabapentin has serious negative consequences. The safety of the use of gabapentin in pregnant women has always been a serious issue, as gabapentin can cross placental barriers. The impact of gabapentin on brain development in the fetus is not sufficiently investigated, which poses difficulties in clinical decisions regarding prescriptions. Methods: The consequences effect of prenatal gabapentin exposure on the development of ventral midbrain dopaminergic neurons were investigated using three-dimensional neuronal cell cultures. Time-mated Swiss mice were used to isolate embryos. The ventral third of the midbrain was removed and used to enrich the dopaminergic population in 3D cell cultures that were subsequently exposed to gabapentin. The effects of gabapentin on the viability, ATP release, morphogenesis and genes expression of ventral midbrain dopaminergic neurons were investigated. Results: Gabapentin treatment at the therapeutic level interfered with the neurogenesis and morphogenesis of vmDA neurons in the fetal brain by causing changes in morphology and alterations in the expression of key developmental genes, such as Nurr1, Chl1, En1, Bdnf, Drd2, and Pitx3. The TH+ total neurite length and dominant neurite length were significantly altered. We also found that gabapentin could halt the metabolic state of these neuronal cells by blocking the generation of ATP. Conclusion: Our findings clearly indicate that gabapentin hampers the morphogenesis and development of dopaminergic neurons. This implies that the use of gabapentin could lead to serious complications in child-bearing women. Therefore, caution must be exercised in clinical decisions regarding the prescription of gabapentin in pregnant women.